Tren Penelitian Etika dan Hak Cipta dalam Perpustakaan: Analisis Bibliometrik - Arya Wijaya Pramodha Wardhana; Ike Iswary Lawanda (Perpustakaan Nasional, 2024)
Ethics and copyright are significant topics within the context of libraries, as libraries play a crucial role as information regulators. This bibliometric study aims to identify research trends related to ethics and copyright in the library context from 2014 to 2024. Data were obtained from the Scopus database using the query term: